(untitled) (Research, Society and Development, 2024)
Objectives: To describe the process of development and dissemination of the Pharmaceutical Observatory website of the Faculty of Pharmacy of the Institute of Health Sciences of the Federal University of Pará, as an innovative technological product, focusing on the production of two dashboards integrated into the platform, on Pharmaceutical Assistance and Covid-19 in the state of Pará, in addition to resulting scientific productions and technical products. Methodology: This is exploratory research, of a descriptive and analytical nature: retrospective (2018, 2019, and 2020) for the recovery of sociodemographic, epidemiological, and health service offering data and information, and cross-sectional (2020, 2021, and 2022) for the situational diagnosis of pharmaceutical assistance of the 144 municipalities of the state of Pará, adopting the precepts of Action Research. Results and Discussion: Dashboards on the situational diagnosis of the Institutionalization of Pharmaceutical Assistance in the 144 municipalities of the State of Pará and on the profile of indicators on the morbidity and mortality of COVID-19 in the 13 Health regions of Pará. Conclusion: The Pharmaceutical Observatory of the Faculty of Pharmacy of the Institute of Health Sciences of the Federal University of Pará is a potential strategy for knowledge dissemination about Pharmaceutical Assistance in the context of Public Health in Pará State.